Dynamic Modelling of Piston the Motion in Combustion Engines - Sunny Narayan; Shitu Abubakar; Muhammad Usman Kaisan; Hauwa Ndagi; Yunusa Tukur; Ivan Grujić; Nadica Stojanović (Communications - Scientific letters of the University of Zilina, 2022)
The presented work discusses a methodology for analysis of noise emissions from a diesel engine. A numerical model of the piston motion, analyzing its lateral, reciprocating and rotation motion, has been presented in order to investigate the lateral motion of the piston skirt assembly and resulting vibrations induced as a result of these motions in the engine block. Various parameters of modal analysis were obtained using the mobility analysis. The presented methodology was validated by data obtained from a diesel engine test set up. The predicted results matched well with those of measured data, hence validating the presented scheme.